Kualitas Audit, Capital Intensity dan Ukuran Perusahaan Terhadap Tax Avoidance Pada Perusahaan Farmasi Yang Terdaftar di BEI Periode 2016 Sampai 2020 - Desy Septariani; Ria Susanti Johan; Widiyarini Widiyarini (Sosio e-Kons, 2022)
This research aims to get empirical evidence about the effect of audit quality, capital intensity, and firm size on tax avoidance. The type of data used is secondary data obtained from IDX (Indonesia Stock Exchange) and ICMD (Indonesian Capital Market of Directory) from 2015 until 2019. The Population of this research is all pharmaceutical companies in the Indonesian Stock Exchange period 2016 until 2020. The sampling method uses purposive sampling method, in which 8 pharmaceutical companies were selected as samples. The analysis method used is multiple linear regression with program SPSS (Statistic Program for Social Science) with a significance level of 0.05. Hypothesis testing used in this research is f test and t-test. The results indicate that Partially variable audit quality had a negative and significant effect on the tax avoidance of the pharmaceutical companies listed on the Indonesia Stock Exchange. While the variable capital intensity and firm size had a positive and significant effect on the tax avoidance of the pharmaceutical companies in the Indonesia Stock Exchange period from 2016 until 2020. Simultaneously audit quality, capital intensity, and firm size have significant influences on tax avoidance. The next research to increase the variables that influence tax avoidance are corporate governance, earning management, audit committee, inventory intensity, and sales growth.